The effect of sintering temperture to the microstructure of PM F75 (Co-Cr-Mo) alloy - Mohd Tajuddin Mohd Idris (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.